Efficient One-Pot Synthesis of 2H-indazolo[2,1-b]phthalazine-1,6,11-trione Derivatives Catalyzed by Y(OTf)3 - Turhan, K.; Turgut, Z. (PLEIADES PUBLISHING LTD, 2019)
In this study, substituted 2H-indazolo[2,1-b]phthalazine-1,6,11-triones, that may possess biological activity, have been synthesized via one-pot three-component cyclocondensation reaction of aromatic aldehydes, cyclic 1,3-dione and phthalhydrazide in ethanol catalyzed by Y(OTf)(3) with good to excellent yields. The structures of all synthesized compounds, 3,4-dihydro-13-phenyl-2H-indazolo[2,1-b]phthalazine-1,6,11(13H)-trione (4a), 13-(4-cyanophenyl)-3,4-dihydro-2H-indazolo[2,1-b]phthalazine-1,6,11(13H)-trione (4b), 3,4-dihydro-3,3-dimethyl-13-(4-cyanophenyl)-2H-indazolo[2,1-b]phthalazine-1,6,11(13H)-trione (4c), 3,4-dihydro-3,3-dimethyl-13-phenyl-2H-indazolo[2,1-b]phthalazine-1,6,11(13H)-trione (4d), and 3,4-dihydro-13-(4-isopropylphenyl)-3,3-dimethyl-2H-indazolo[2,1-b]phthalazine-1,6,11(13H)-trione (4e) have been elucidated from IR, NMR and mass spectral data.
Keywords: indazolo[2,1-b]phthalazine-trione; green chemistry; one-pot; multicomponent; Y(III) triflate; IONIC LIQUID; SOLVENT-FREE; Chemistry